PROGRAM PENDIDIKAN KARAKTER DALAM PEMBELAJARAN PAI SD/MI - Sri Purwanti (CV Putra Publisher, 2022)
In the world of education, the obligation of schools is not only to provide knowledge to students but more than that, namely to foster student character so that a personality with good character is achieved. The purpose of this study was to analyze character education programs related to learning Islamic Religious Education in Basic Education. This research method uses a qualitative liberary research approach that uses primary data sources from studies of research journals and relevant books related to character education programs. The results of this study state that the character education program will be built if there is good cooperation between the family, school and community environment. In addition, character education programs must be strengthened in the family environment because time at home is longer than at school so that the implementation of character education programs will be realized at the age of elementary children.